2013
DOI: 10.1021/nn4002006
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Metal Adhesion Layers That Do Not Deteriorate Plasmon Resonances

Abstract: G reat amounts of numerical and experimental investigations have been devoted to boosting the signal of plasmonic sensors fabricated from noble metal nanoantennas with sharp edges or with gaps separated by a few nanometers. 1À8 The field enhancement depends mainly on the ability to couple incident photons to localized surface plasmon modes. Such resonant modes are prone to damping by scattering and absorption in the metal and its surrounding materials, thus, limiting the achievable enhancement. 9 By interfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 39 publications
5
94
0
1
Order By: Relevance
“…Previous work studying the effects of a Ti adhesion layer on the plasmonic response of an Au nanostructure to incident light illumination has shown that the optical enhancement produced by the structures decreases with increasing Ti layer thickness. [64][65][66][67][68] Therefore, for optical applications, ideally no adhesion layer would be used, but in the case in which it is required, the smallest possible adhesion layer should be used to preserve the optical characteristics of the patterned structures. The thickness of the Au layer has also been found to significantly affect the optical response of a patterned nanostructure, with and without nanoslits.…”
Section: Nanomasking Fabricationmentioning
confidence: 99%
“…Previous work studying the effects of a Ti adhesion layer on the plasmonic response of an Au nanostructure to incident light illumination has shown that the optical enhancement produced by the structures decreases with increasing Ti layer thickness. [64][65][66][67][68] Therefore, for optical applications, ideally no adhesion layer would be used, but in the case in which it is required, the smallest possible adhesion layer should be used to preserve the optical characteristics of the patterned structures. The thickness of the Au layer has also been found to significantly affect the optical response of a patterned nanostructure, with and without nanoslits.…”
Section: Nanomasking Fabricationmentioning
confidence: 99%
“…17,28 A 1-nm-thick Cr layer evaporated under normal incidence forms an effective adhesion layer which does not affect the plasmonic performance of the system. 29 The cross-section and top-view SEM images of the obtained sub-10 nm gap arrays are shown in Figure 1a and b.…”
Section: −24mentioning
confidence: 99%
“…Commonly, thin layers (nanometers) of Ti, Cr, or other metals are used as the adhesive. 49 Nanofabrication techniques usually deposit a semiuniform layer of the adhesion material prior to deposition of the desired metal. Although usually necessary, it has been shown that this layer produces "damping" effects of the plasmonic enhancement that occurs in the near-field of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Although usually necessary, it has been shown that this layer produces "damping" effects of the plasmonic enhancement that occurs in the near-field of the structure. 49 In the nanomasking process utilized by the Herzog group, a Ti adhesion layer is most commonly used because a sacrificial Cr layer is required for the fabrication process. 47 Thus, the current work studies the effects of varying the thickness of a Ti adhesion layer on the local plasmonic field enhancement.…”
Section: Introductionmentioning
confidence: 99%